Current challenges and future opportunities of phage therapy - Pires, Diana P. (2020)
Antibiotic resistance is a major public health challenge worldwide, whose implications for global health might be devastating if novel antibacterial strategies are not quickly developed. As natural predators of bacteria, (bacterio)phages may play an essential role in escaping such a dreadful future. The rising problem of antibiotic resistance has revived the interest in phage therapy and important developments have been achieved over the last years. But where do we stand today and what can we expect from phage therapy in the future? This is the question we set to answer in this review. Here, we scour the outcomes of human phage therapy clinical trials and case reports, and address the major barriers that stand in the way of using phages in clinical settings. We particularly address the potential of phage resistance to hinder phage therapy and discuss future avenues to explore the full capacity of phage therapy.